A educação na televisão interativa: ensino e aprendizagem cognitivos na migração digital - Alonso, Renato Almada (2016)
The research investigates the ways that interactive television leaves as margin to pedagogical studies. The proposal is to offer educators, producers and instructional designers a new look on the construction of teaching and learning from the documentation of cognitive processes in a unique environment, which reconstitutes the hybrid technology and comprises a modern and peculiar media. For this, it was necessary a chronological study of educational spaces, which was understandable the size of a mass communication medium as distance learning. A second analysis of new scenarios and the components of this process explains the procedural aspect of relations man-machine and its culture, in order to position the participating actors in this environment. Finally, we deepen the documentary analysis in interactive television, considering the human perspective as object and establishing a dialogue with education and vehicles, looking out over its intricate corpus. The analysis is based on the contribution of authors like Gauthier, Tardif, Moran, Moore, Kearsley, Perrenoud, Gobbi, Kerbaui, Filatro, Vilches, Mininni, Santaella, Behar, Lévy, Mattar and Lemos. Your thoughts are fundamental to a detailed research about the topic. From the point of view of studies on the process of creating content for interactive television, the research establishes a dialogue between the fields that form educommunication, seeking to deepen the understanding of the viewer / student relationship and bringing contributions to enable the construction of its identity. For professionals, it is expected that through the exchange of information from this research, may be possible to understand within the complexity of technology and seriousness that the mass media should be treated